Schaum's outline of theory and problems of partial differential equations - Duchateau, Paul (Tata McGraw-Hill, 2005)
Schaum's outline of theory and problems of partial differential equations / Duchateau, Paul. -- New Delhi: Tata McGraw-Hill, 2005 515.353 D827 No. of Copies : 1